Study of the application of solar cells in public lighting - Faustino, Rafael; Lameirinhas, Ricardo Alexandre Marques; Bernardo, Catarina Pinho Correia Valério; Torres, João Paulo Neto; Santos, Marcelino (International Journal of Innovative Research and Scientific Studies, 2025)
As a result of climate change, there has been increasing interest in renewable energies. The state of the planet is worsening to such an extent that it is already seen as absolutely necessary to replace fossil fuels with other, more sustainable solutions. With this objective in mind, this research work aims to study a project that powers a public lighting system using photovoltaic energy. The study site is the Alameda Garden, where the project will have to supply 8,410 W. To this end, a study and framework are provided on the state and evolution of photovoltaic technology and the choice and characteristics of the implementation site. With the financial results, production, consumption, energy made available, and other factors that influence the viability of the project, the solutions presented are compared, giving an opinion on which is the best and the challenges that still exist and that can be tackled in the future. In the end, it is possible to conclude that the project is not financially viable on its own. Since it is not possible to sell energy to the grid, the project’s only income is the energy saved during the night. Due to the characteristics of the loads to be powered, batteries are needed, which are expensive components; therefore, it is not possible to recover the investment after 20 years. Thus, it is concluded that in this project’s types, one may also consider the social and environmental impacts besides the financial indicators.